2018
DOI: 10.1177/0300060518765310
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute tandem occlusions: Stent-retriever thrombectomy with emergency stenting or angioplasty

Abstract: ObjectiveTo compare outcomes following intracranial stent retriever-based intracranial thrombectomy (SRT) with emergency extracranial internal carotid artery (EICA) stenting or angioplasty alone in patients presenting with acute stroke due to tandem occlusions of the ICA.MethodsConsecutive patients with acute anterior tandem occlusion who received an endovascular intervention within 6h of symptom onset between January 2013 and June 2016 were included in this prospective study. Demographic, radiological, proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 30 publications
0
28
1
Order By: Relevance
“…Only few previous studies investigated the rate of distal embolization according to the interventional technique. Li et al reported that they found higher distal embolic rate in the angioplasty only group [31]. However, occurrence of distal embolization in our study was significantly higher in patients with ACS (39.1% vs. 17.9%, p = 0.043).…”
Section: Discussioncontrasting
confidence: 75%
“…Only few previous studies investigated the rate of distal embolization according to the interventional technique. Li et al reported that they found higher distal embolic rate in the angioplasty only group [31]. However, occurrence of distal embolization in our study was significantly higher in patients with ACS (39.1% vs. 17.9%, p = 0.043).…”
Section: Discussioncontrasting
confidence: 75%
“…Antiplatelet strategies by those advocating stenting in this setting typically involve pre-or peri-procedural dual oral antiplatelet or intravenous glycoprotein IIb/IIIa inhibitor loading followed by maintenance therapies, 4)13)34) although holding antiplatelets for 24 hours after tPA despite stent placement has also been described. 22) This latter approach likely derives from the current stroke guidelines that advise against the administration of antiplatelets within 24 hours of tPA, 33) and are based on RCTs that demonstrated increased ICH risk without improved outcomes for the early administration of aspirin after tPA. 41) However, these studies did not account for the increased thrombotic risk in patients undergoing MT or stent placement, a consideration highlighted by the in-stent thrombosis seen in the one patient in this study that had delayed initiation of post-procedural antiplatelets.…”
Section: Discussionmentioning
confidence: 99%
“…Successful recanalization rate was statistically significantly higher in the stenting group than in the angioplasty-alone group (74 vs. 39%) and although not statistically significant, more patients in the stent group than in the angioplastyalone group had favorable outcomes (63 vs. 50%). 23 The STRATIS Registry included 147 patients with tandem lesions. Eighty patients underwent carotid stent placement, 43 patients underwent balloon angioplasty, and 24 patients did not undergo angioplasty or stent placement.…”
Section: Should the Carotid Occlusion Be Treated With Balloon Angioplmentioning
confidence: 99%